Inter-religious relations in South Africa with reference to Christians and Muslims - Dolamo, RTH (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
This article is in the realm of religious pluralism and ecumenism. It is about the relation between Christianity and Islam as it unfolded in the Cape since 1652 and in the entire country to date. Christianity, as embodied in the Dutch Reformed Church, was the religion of the ruler whilst other religions and even other churches were not allowed to operate freely and publicly in the Cape colony. Freedom of religion was eventually granted in 1804. As we celebrated in 2004, ten years of freedom and democracy, and thus of two hundred years of religious freedom, this article looks at what has accrued to South Africa’s religious heritage in terms of inter-religious dialogue and praxis as well as ecumenical relations.